A Comparative Study on Satellite Image Classification Using Various Deep Learning Techniques (INTERNATIONAL SCIENTIFIC INNOVATION RESEARCH CONFERENCE, 2024)
The satellite image classification procedure comprises categorizing the image pixel values. There are several approaches and procedures for classifying satellite images. Satellite image categorization algorithms are roughly divided into three categories: 1) automatic 2) manual and 3) hybrid. Satellite image classification requires the selection of an appropriate classification method depending on the criteria. This paper focuses on satellite image categorization methods and methodologies.